EKPLORASI ETNOMATEMATIKA PADA BANGUNAN BERSEJARAH BENDUNGAN WALAHAR TERHADAP PEMBELAJARAN MATEMATIKA - Agustin, Siti Sundari; Soebagyo, Joko (SJME (Supremum Journal of Mathematics Education), 2024)
The mathematics learning process will be effective if there is social and cultural interaction through dialogue, language and representation of symbolic meaning in mathematics. Therefore, integrating ethnomathematics as a cultural value is part of representing real environmental objects in mathematical concepts. The aim of this research is to explore mathematical concepts in the historical building of the Walahar Dam and the implications for mathematics learning. This type of research uses descriptive exploratory. Research data was collected through interviews, observation and documentation. Meanwhile, the data analysis carried out was analyzing flat shapes which were adapted to mathematics learning. The results of this research can be concluded that one of the cultural heritage heritage of the Netherlands is a historical building, namely the Walahar Dam which has flat shapes such as an isosceles triangle, circle, rectangle and a flat shape that is a combination of a rectangle and a semi-circle. To encourage students to actively participate in exploring sources that are relevant to the material being studied. This allows students to connect the contextual environment and their knowledge experiences when learning mathematics.